2016
DOI: 10.1007/s11606-016-3609-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Decision Aids with Minority Patients: a Systematic Review

Abstract: BACKGROUND:One potential approach to reducing health disparities among minorities is through the promotion of shared decision making (SDM). The most commonly studied SDM intervention is the decision aid (DA). While DAs have been extensively studied, we know relatively little about their use in minority populations. We conducted a systematic review to characterize the application and effectiveness of DAs in racial, ethnic, sexual, and gender minorities. METHODS: We searched PubMed for randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…All of the studies focused on HIV infection and none dealt with African-American women who were sexual minorities or African-American transgender men. While research indicates that decision-aids can improve shared decision making among racial/ethnic minorities, 83 none of our studies identified clinical tools such as decision aids to assist in SDM among African-American LGBT persons. And although concerns about healthcare discrimination and other organizational factors (e.g., loss of privacy) were noted themes, we did not find any organizational or clinician interventions to improve SDM among this population.…”
Section: Discussionmentioning
confidence: 82%
“…All of the studies focused on HIV infection and none dealt with African-American women who were sexual minorities or African-American transgender men. While research indicates that decision-aids can improve shared decision making among racial/ethnic minorities, 83 none of our studies identified clinical tools such as decision aids to assist in SDM among African-American LGBT persons. And although concerns about healthcare discrimination and other organizational factors (e.g., loss of privacy) were noted themes, we did not find any organizational or clinician interventions to improve SDM among this population.…”
Section: Discussionmentioning
confidence: 82%
“…104 Best practices for implementing and evaluating DAs exist, but do not address minority patients specifically. 105,106 Preliminary evidence suggests that DAs can improve communication and psychological outcomes for racial/ethnic minority populations; however, existing decision aids cover a limited range of topics and rarely address LGBT patients. 106 Tailored educational materials support patient satisfaction, understanding, and adherence to treatment.…”
Section: Decision Aids and Educational Materialsmentioning
confidence: 99%
“…105,106 Preliminary evidence suggests that DAs can improve communication and psychological outcomes for racial/ethnic minority populations; however, existing decision aids cover a limited range of topics and rarely address LGBT patients. 106 Tailored educational materials support patient satisfaction, understanding, and adherence to treatment. 42,43 For most minority patients, cultural tailoring goes beyond language 107 and literacy; 108 for example, LGBT-specific educational materials can help LGBT patients discuss their options and preferences with clinicians.…”
Section: Decision Aids and Educational Materialsmentioning
confidence: 99%
“…[6][7][8] The three papers outline a conceptual model for SDM with LGBT racial/ethnic minority patients, and then present information that may guide interventions to assist individual clinicians and patients in improving their SDM, and may help health care organizations transform their structures to facilitate SDM.…”
mentioning
confidence: 99%
“…In a systematic review, Nathan et al found that decision aids have improved communication and psychological outcomes in racial/ethnic minority populations. 7 However, they identified only one study of decision aids in sexual minorities and none for transgender patients.…”
mentioning
confidence: 99%